Prácticas de enseñanza de lengua y literatura en educación general básica :análisis de caso en segundo año en la Escuela Diez de Agosto del cantón Otavalo - Flores Coral, Lupe Janeth (2016)
This research seeks to observe teaching practices at the School August 10 in the city of Otavalo, during 2014-2015 school year in the latter years of General Basic Education, they are considered in this work aspects such as planning, methodological structure , the organization of work of subject, teacher student interaction, assessment strategies class issue, the types of academic tasks. Theoretical elements that guide the teaching level state guidelines are addressed, the definition of educational practice is analyzed and disclosed the standards that exist on the area of language arts. A case study was conducted field research, using techniques such as observation, interview and field diary, document review, these elements the theory behind the subject were analyzed. The results of observations in the teaching process of teaching are presented.